2019
DOI: 10.1007/s00418-019-01824-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-related glomerular lesions with albuminuria in male cotton rats

Abstract: The increased prevalence of aging-related chronic kidney disease (CKD) among humans is a problem worldwide. Aged cotton rats (Sigmodon hispidus) are considered novel model animals for studying CKD, especially as the females develop severe tubulointerstitial lesions with anemia. To investigate the renal pathologic features in aged male cotton rats and their characteristic glomerular injuries, the animals were divided into young, adult, old-aged, and advanced-aged groups (1-4, 5-8, 9-12, and 13-17 months, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Plasma Cr is a more specific factor than urea level to evaluate kidney function; because Cr has all the features needed for a perfect filtration indicator. It was revealed that elevation of urea and plasma Cr along with a reduction of plasma albumin level occurs in nephropathy (23). The increase of BUN and Cr levels are related to glomerular filtration dysfunction caused by DG.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma Cr is a more specific factor than urea level to evaluate kidney function; because Cr has all the features needed for a perfect filtration indicator. It was revealed that elevation of urea and plasma Cr along with a reduction of plasma albumin level occurs in nephropathy (23). The increase of BUN and Cr levels are related to glomerular filtration dysfunction caused by DG.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to NPH, cotton rats have noticeable unique phenotypes in the urinary, circulatory, reproductive, digestive, and integumentary systems, including systemic pathological phenotypes, such as chronic kidney disease and metabolic disorders. [10][11][12][13][14] Thus, cotton rats might also be useful for researching the comorbidities of NPH in other diseases. In conclusion, cotton rats may serve as a novel and useful model for elucidating the pathomechanism of hydrocephalus, particularly idiopathic NPH.…”
Section: Discussionmentioning
confidence: 99%
“…We here report that cotton rats have noticeable systemic pathological phenotypes, such as chronic kidney disease with anemia, metabolic disorders, and false caudal autotomy. [10][11][12][13][14] Additionally, these species possess unique phenotypes in endocrine, reproductive, and digestive organs, [15][16][17][18] suggesting that cotton rats might be useful experimental animal models. However, the central nervous system (CNS) of cotton rats has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains unknown as to the mechanisms underlying this sex difference. Given the essential role of podocytes in glomerular filtration barrier integrity [ 24 ], and considering that Arg-II may potentially be upregulated in injured podocytes [ 23 ], this work aimed to investigate whether Arg-II is elevated with aging in podocytes, contributing to the age-associated increase in albuminuria in a natural aging mouse model.…”
Section: Introductionmentioning
confidence: 99%